Subjective evaluation of luteal irrigation rate as diagnostic tool for pregnancy at 21 days on cows (Research, Society and Development, 2022)
There is an increasing demand for validated techniques, with real time feedback, aiming to a higher reproductive efficiency on dairy herds. The objective of the current study was to evaluate the sensitivity, specificity and accuracy of early pregnancy diagnosis, on dairy cows, 21 days after AI, based on subjective evaluation of luteal irrigation rate. 316 ultrasound examinations were observed. 21 days after AI, the cows were assessed with color Doppler ultrasonography, performing a subjective classification of corpus luteum: poor irrigation, good irrigation or great irrigation. Cows with corpus luteum of poor irrigation were considered non-pregnant, and cows with good or great irrigation were considered as pregnant. The determination of sensitivity, specificity and accuracy was made by considering the definitive pregnancy diagnosis 27 days after AI. The sensitivity observed was 86,5%, specificity of 44,3% and accuracy of 69.8%. The early pregnancy diagnosis on dairy cows based on evaluation of luteal irrigation rate, 21 days after AI, could be useful on optimization of reproductive management of herds and should be considered as an option at the time of choice of the pregnancy diagnosis technique.